From Awareness to Action: Medan's Youth Pioneering Religious Moderation as a Tool Against Radicalism - Sukri, Al; Mailin; Sazali, Hasan (JURNAL PENELITIAN, 2024)
Preventing radicalism among youth is a crucial challenge in the modern era, particularly in major cities like Medan, which have a high level of religious diversity. This research is essential due to the potential conflicts that may trigger social instability. The aim of this study is to explore strategies that can be implemented to educate and equip adolescents with religious moderation literacy, considering the rising tendency of radicalism that could disrupt social stability. The methodology used is qualitative, employing a phenomenological approach, which includes in-depth interviews, participatory observations, and document collection. Data were gathered from students and young people in Medan to understand their perspectives on religious moderation. The findings of the study suggest that religious moderation literacy can be fostered through several means, such as youth involvement in the creation of digital content, interfaith mentorship programs, and the establishment of interfaith youth networks. Community-based training and the utilization of social media as a tool for disseminating information also play a significant role in shaping moderate attitudes. These findings indicate that enhancing moderate religious literacy can reduce the potential for radicalization among youth, while simultaneously fostering a better climate of tolerance within society.